Transient Blood Brain Barrier Disruption Induced by Oleic Acid is Mediated by Nitric Oxide - Soo Han, Hyung; Hee Jang, Jae; Sik Park, Jae; Jin Kim, Hak; Kun Kim, Jong (Current Neurovascular Research, 2013)
The blood brain barrier (BBB) maintains cerebral microenvironmental homeostasis. Transient disruption of the BBB after brain fat embolism in clinical cases and animal models has been reported but the precise mechanism underlying this occurrence is unclear. In the present study, we investigated BBB alterations in rats treated oleic acid (OA) delivered intra-arterially. Following OA treatment, transient brain edema, extravasation of Evans blue and Fluorescein isothiocyanate (FITC)-labeled dextran, and loss of laminin in the affected brain area were observed. Activation of matrix metalloproteinase (MMP)-2, -3, and -13 was found in the cerebral vessels 2 h after OA administration. Expression of intercellular adhesion molecule (ICAM)-1 in the vessels and neutrophil infiltration into the brain tissue was also observed. Inducible nitric oxide synthase (iNOS) was expressed in the neutrophils and nitrotyrosine was produced mainly in the vessels. Inhibitor of iNOS activity suppressed the loss of laminin, leakage of FITC-labeled dextran and Evans blue, and activation of MMP-2 and -13. Protein level of aquaporin (AQ)-4 was increased after OA administration but was not affected by treatment with iNOS inhibitor. In conclusion, we suggest that nitric oxide (NO) contributes to OA-induced MMP activation, BBB disruption and the development of transient brain edema.
Keywords: Blood brain barrier (BBB)